The Implementation of Project Based Learning in English Language Teaching at Rural School: A Conceptual Review - Muttahidah; Laily Zen, Evynurul (Universitas Cokroaminoto Palopo, 2023)
Teaching English as a foreign language in a rural education is challenging. Due to the fact that most schools located in rural areas are not equipped with audio visual aids, it affected the learning strategies used by the teachers which only focus on grammar and mainly use L1 translation. To overcome those problems and also equip students with 21st century skills, Project-Based Learning (PjBL) can be an alternative. Many studies related to PjBL in the EFL context have been conducted and provided benefits. Considering the benefits of PjBL, this paper tries to explore more closely the current practices of PjBL in the EFL context. Using library research by collecting some related books and articles, this paper explained the concept, the procedures, and the assessment of PjBL. It also described the strengths and the weaknesses of applying PjBL in the EFL context. Furthermore, this paper presented some teaching techniques in PjBL which can be applied to promote EFL students’ language skills at rural schools. This review will give an implication for English teachers, especially at rural schools in understanding the concept and practice of PjBL which promotes 21st century skills.